Human Adipose-Derived Mesenchymal Stromal Cells May Promote Breast Cancer Progression and Metastatic Spread. Issue 1 (July 2015) - Kamat, Pranitha; Schweizer, Riccardo; Kaenel, Philip; Salemi, Souzan; Calcagni, Maurizio; Giovanoli, Pietro; Gorantla, Vijay S.; Eberli, Daniel; Andres, Anne-Catherine; Plock, Jan A.
Abstract : Background: Stem cell–enriched fat grafting has been proposed as a potential therapy for reconstructive, restorative, or enhancement-related procedures of the breast. Its role in postoncologic breast reconstruction is still emerging, with concerns about safety. The authors investigated the dose-dependent interaction between human adipose-derived mesenchymal stromal cells (AD-MSCs) and human breast cancer cell (BCC) lines [MDA-MB-231 (MDA) and MCF-7 (MCF)] focusing on tumor microenvironment, tumor growth, and metastatic spread. Methods: Adipose-derived mesenchymal stromal cell influence on viability and factor expression [regulated on activation, normal T cell expressed and secreted (RANTES), tumor necrosis factor-α, and eotaxin) of breast cancer cells was studied in vitro using direct and indirect co-culture systems. Groups were formed according to adipose-derived mesenchymal stromal cell–to–cancer cell number ratio [MDA/MCF only, AD-MSC low /(MDA/MCF), and AD-MSC high /(MDA/MCF)]. A humanized orthotopic murine cancer model was used to evaluate breast cancer progression and metastasis ( n = 10/group). Cells were injected into the mammary pad in different ratios and animals were monitored over 42 days. Microdialysis was performed to analyze RANTES levels in the tumor microenvironment (days 21 and 42). Primary and metastatic tumors were weighed and analyzed for oncogene, growth factor, and metastatic marker expression. Results: MDA cell viability increased from 45.5 percent to 95.5 percent in presence of adipose-derived mesenchymal stromal cells in vitro. In vivo, animals with AD-MSC high showed increased mean tumor weight (MDA, p < 0.01; MCF versus controls, p < 0.05) and metastatic occurrence (40 percent in MDA; 30 percent in MCF versus 0 percent in controls). Cytokine analysis revealed switching of MCF tumor phenotype to a more malignant type in the presence of adipose-derived mesenchymal stromal cells. Conclusion: Human adipose-derived mesenchymal stromal cells may promote progression and metastatic spread in breast cancer through a switch to a more malignant phenotype with worse prognosis. Abstract : Supplemental Digital Content is available in the text.